A Comprehensive Numerical Study on Thermohydraulic Performance of Fluid Flow in Triangular Ducts with Delta-Winglet Vortex Generators - Akcayoglu, Azize; Nazli, Celal (Informa UK Limited, 2017)
Triangular ducts fitted with various kinds of delta-winglet type vortex generators (VGs) are commonly used to achieve compactness and heat transfer enhancement in many industries. Successive locati...
Keywords: 11. Sustainability